Shakespeare and Canada : Remembrance of Ourselves - Brisset, Annie (Book collections on Project MUSE., 2017)
As we commemorate the 400th anniversary of William Shakespeare's death, the most translated and performed playwright in the world continues to live on in our imagination. How might we historicize Shakespeare's influence in Canada?